LITERASI BUDAYA BALI: MENGEMBANGKAN EMPATI SISWA MELALUI KISAH MEN SUGIH LAN MEN TIWAS (KAJIAN LITERATUR) - I Wayan Sujana; Ida Bagus Yoga Swadnyana; Ni Putu Evi Puspita; Ni Putu Ayu Wulandari Putri; Komang Anggun Sugiantari (STKIP Subang, 2026)
This study aims to examine the role of Balinese cultural literacy through the use of Satua Bali Men Sugih lan Men Tiwas in developing empathy in elementary school students. The study used a literature review method by examining relevant scientific sources, such as journals, books, proceedings, and official documents published in 2022–2026. Data collection was carried out through a systematic literature search using keywords related to cultural literacy, student empathy, character education, and Balinese folklore. Data were analyzed using content analysis techniques to identify the values of empathy and character contained in Balinese folklore and their relationship to learning in elementary schools. The results of the study indicate that strengthening character education is important from an early age to face challenges of technological development and globalization that can influence student behavior. Satua Bali as local cultural heritage has moral, social, and spiritual values that can be utilized as a contextual learning medium to instill empathy, social awareness, responsibility, and appreciation for regional culture. The story of Men Sugih and Men Tiwas teaches students to understand the feelings of others, help each other, and not discriminate based on socioeconomic background. Furthermore, the use of Balinese folklore in learning can improve students' literacy skills, such as reading, listening, speaking, and understanding the meaning of the story. Therefore, the use of Satua Bali in elementary school learning can be an effective tool for developing empathy, strengthening character, and preserving Balinese culture in the younger generation and supporting meaningful learning in schools.